Teaching Learning Mathematics in Multi-cultural Classroom - Giri, Shivahari (Mangal Research Journal, 2021)
In the multicultural classroom, students come from many different back-grounds, experiences, and ethnicities. As a result of poor performance in traditional mathematics assessments, teachers often believe English language learners to be weak students. This study aims to unveil the experiences of mathematics teachers while engaging students in multicultural classrooms and describing their ethnic and cultural influence in primary level mathematics teaching in the context of Nepal. The study focused on finding the reasons of the irregularity of the students, the use of their non - contextualized vocabularies and various other challenges faced by teachers in a multicultural classroom. This study underpins qualitative research design under which I applied phenomenological approach and in-depth interviewed six primary level mathematics teachers in Kirtipur Municipality. The data management was conducted through thematic analysis. The main finding of the study is that the teachers used different strategies that allowed the students to reason and communicate mathematically and develop students’ abilities to solve problems. They acted in playing the role of facilitators to accomplish their professional responsibility. The study also revealed that the students, teachers, parents, environment and national policies are all responsible to influence the learning activities of the students. Moreover, teachers’ experiences help in motivating the learners and promoting the teaching learning activities in the multi-cultural classroom.